Recent Acquisitions - Stephanie Archangel; Jeroen ter Brugge; Jan Pelsdonk; Eveline Sint Nicolaas; Harm Stevens (The Rijksmuseum Bulletin)
As there is often a tendency for the knowledge of surface perception and material processes to become lost amidst written art historical sources and analytical results, joining the expertise of art history and art conservation proved invaluable in the interpretation of the appreciation of the lacquer caskets of Willem Kick (1579-1647). A reconstruction gave valuable insights into art-technological processes and shed further light on Kick’s workshop practice, bringing us closer to understanding the original state and appreciation of his works and of the objects now on display in the Rijksmuseum.